2020
DOI: 10.33549/physiolres.934142
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Sesamin in Cisplatin-Induced Nephrotoxicity in Rats by Suppressing Inflammation, Oxidative/Nitrosative Stress, and Cellular Damage

Abstract: Nephrotoxicity of cisplatin (CP) involves renal oxidative stress and inflammation, and sesamin (a major liganin in many plants) has strong antioxidant and antiinflammatory actions. Therefore, we investigated here the possible mitigative action of sesamin on CP nephrotoxicity in rats. Sesamin was given orally (5 mg/kg/day, 10 days), and on the 7th day, some of the treated rats were injected intraperitoneally with either saline or CP (5 mg/kg). On the 11th day, rats were sacrificed, and blood and urine samples a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
4
9
0
Order By: Relevance
“…interferon γ (IFNγ)-inducible protein 10 (IP-10/CXCL10)) in human primary monocytes and THP-1 cells ( Hsieh et al, 2014 ). The anti-inflammatory effects of sesamin have also been observed in different in vivo models ( Cui et al, 2010 , Lin et al, 2014 , Ahmad et al, 2016 , Zhang et al, 2016 , Li et al, 2016 , Fan et al, 2017 , Rousta et al, 2018 , Zhao et al, 2019 , Bai et al, 2019 , Lin et al, 2019 , Sayhan et al, 2019 Ali et al, 2020 ). Consistently, sesamin has been shown to suppress a series of inflammatory markers associated with type-II diabetes and rheumatoid arthritis in humans ( Mohammad Shahi et al, 2017 , Helli et al, 2019 ).…”
Section: Anti-inflammatory Effects Of Sesaminmentioning
confidence: 91%
“…interferon γ (IFNγ)-inducible protein 10 (IP-10/CXCL10)) in human primary monocytes and THP-1 cells ( Hsieh et al, 2014 ). The anti-inflammatory effects of sesamin have also been observed in different in vivo models ( Cui et al, 2010 , Lin et al, 2014 , Ahmad et al, 2016 , Zhang et al, 2016 , Li et al, 2016 , Fan et al, 2017 , Rousta et al, 2018 , Zhao et al, 2019 , Bai et al, 2019 , Lin et al, 2019 , Sayhan et al, 2019 Ali et al, 2020 ). Consistently, sesamin has been shown to suppress a series of inflammatory markers associated with type-II diabetes and rheumatoid arthritis in humans ( Mohammad Shahi et al, 2017 , Helli et al, 2019 ).…”
Section: Anti-inflammatory Effects Of Sesaminmentioning
confidence: 91%
“…It also abrogated LPS-induced acute kidney injury via the attenuation of renal oxidative stress, inflammation, and apoptosis, and returning the renal oxidative stress-related parameters [ 169 ], thereby demonstrating potential against injuries in septic conditions. Sesamin possessed mitigative action on cisplatin (CP) nephrotoxicity in rats by reversing the CP-induced oxidative stress and inflammation [ 170 ]. In addition, sesamin significantly alleviated fluoride-induced renal oxidative stress and apoptosis of carp Cyprinus carpio [ 165 ].…”
Section: Lignans With Antioxidant and Anti-inflammatory Actionmentioning
confidence: 99%
“…It is highly distributed in the liver and kidney as sesamin metabolites and plays various physiological effects such as antioxidant [ 12 ], anti-inflammatory [ 13 ], a protective role against mitochondrial toxicity [ 14 ], a lowering effect on serum cholesterol, lipid level, and blood pressure [ 15 , 16 ], a protective effect against alcohol-induced liver injury [ 17 ] and anti-allergic effect [ 18 ], etc. A recent study published by B H Ali (2020) [ 19 ] indicated sesamin ameliorated cisplatin-induced nephrotoxicity, but cyclophosphamide-induced nephrotoxicity has not been explored yet. Therefore, this idea encourages us to explore the defending action of Sesamin against cyclophosphamide-induced nephrotoxicity.…”
Section: Introductionmentioning
confidence: 99%